ANALISIS PENGARUH HARGA DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN MIE INSTAN MEREK INDOMIE - Petra Paulus Tarigan (Universitas Riau Kepulauan, 2017)
This study aimed to analyze the effect ofprice and brand to brand purchase decisions Indomie instant noodles to students. This research was done by using Slovin Sampling. Samples taken as many as 95 respondents from the students. Data analysis method used is testing instruments made by testing the validity and reliability while data analysis used is descriptive analysis method, multiple linear regression analysis, and hypothesis testing. These results indicate that prices have a significant effect on purchasing decisions with a value of t for 5853 and significant value of 0000; brand and significant influence on purchasing decisions with t value of 3819 and a probability value of 0.000; and simultaneously the price and brand significantly influence the purchase decisions Indomie instant noodle brand in students.